THE PHYLOGENETIC TREE OF Alexandrium Prorocentrum AND PSEUDO-NITZSCHIA OF HARMFUL AND TOXIC ALGAE IN VIETNAM COASTAL WATERS BASED ON SEQUENCES OF 18sRdna, Its1-5.8s-Its2 GENE FRAGMENTS AND SINGLE CELL -PER METHOD - Hong, Dang Diem; Thu, Ngo Thi Hoai; Nam, Hoang Sy; Hien, Hoang Minh; Hai, Luyen Quoc; Ha, Dao Viet; Fukuyo, Yasuo; Iwataki, Mitsunori (Marine Research in Indonesia, 2007)
Molecular biological techniques support the identification of microalgae of Vietnam. Prorocentrum, Alexandrium and Pseudo-nitzschia are main harmful and toxic microalgal genera found in Vietnam coastal waters. The results of morphology and nucleotide sequence analysis of 18S rDNA and ITS 1-5.8S-ITS2 gene obtained from genomic DNA have shown that the Prorocentrum sp. 3 (isolated from Cat Ba, Hai Phong on October, 2004), Alexandrium sp. 5 (collected on October, 2004) and Pseudo-nitzschia sp. G3 (colleted in Do Son, Hai Phong on December, 2005) belonging to Prorocentrum mexicanum (the homological percent of 99.9% with sequencing of P mexicanum in Genbank ofY16232, AY886763), A. minutum (99.8% - AJ535388, DQ168664) and Pseudo-nitzschia pungens (98.8% - AY544769, DQ166533), respectively. The obtained results indicated that the exceptional fresh samples, for Prorocentrum genus which may be preserved at 25% ethanol, 4% formaldehyde, 1% glutaraldehyde, while Alexandrium genus ó at 25% ethanol, and Pseudo-nitzschia genus - 4% formaldehyde and 1% glutaraldehyde for two weeks have not effected on their analysis of sequences generated by Single Cell PCR method. In these studied samples, the nucleotide sequences obtained from genomic DNA and Single-cell PCR methods were the same with the homological percent more than 99%. Application of this method to samples collected from Phu Quoc Island, southern part of Vietnam, in 27-29, June, 2006 showed that Prorocentrum mican and P sigmoisdes were found.